Pelatihan Pembacaan Al-Qur'an Berbasis Akhir Pekan: Sebuah Model untuk Meningkatkan Keterampilan Tilawah pada Siswa Sekolah Dasar - Muzdalipah Muzdalipah; Najminnur Hasanatun Nida; Muhammad Helmi (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to describe the implementation of the weekend bertilawah program and analyze its contribution to improving the Qur'an recitation skills of students. This study used a qualitative, case study approach. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that the weekend bertilawah program was implemented in a structured manner, utilizing weekends as a more intensive learning space. The learning strategies implemented included direct examples, repeated practice, and personalized guidance tailored to the students' ability levels. This program has been proven to improve Qur'an recitation skills, including tajweed accuracy, clarity of pronunciation, voice quality, and rhythmic mastery. Furthermore, the program also contributed to increasing students' confidence in reciting Qur'anic verses. The program's success was supported by a conducive learning environment, the active role of instructors, and student enthusiasm. However, several obstacles were encountered, such as time constraints, differences in ability among students, and inconsistent attendance. Overall, the weekend bertilawah program is considered effective as a learning alternative for continuously improving Quran recitation skills